Viral marketing: The case of Turkey - Hanna Lewicka (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2017)
The purpose of this paper is to present and analyze successful viral marketing campaigns of Turkish advertisements in the form of a case study to determine which factors seem to play the most important role in terms of viral marketing message perception in Turkey. As a country in which the increasing role of digital media and the internet is beginning to dominate interpersonal communication, the use of viral approach in marketing is also growing. The examples of most viral videos in Turkey from the previous years confirm that the most important factor which determines the success of a viral message is its content, which should be at the same time attention-catching and entertaining. Nevertheless, the seeding strategy is the factor which accelerates the success of viral messages.
Keywords: M31; M37; 650; viral marketing; Turkey; advertising; digital media